Tradutor e intérprete de Libras: construção da formação profissional - Giamlourenço, Priscila Regina Gonçalves de Melo (2018)
The process of deaf people inclusion in different social spaces becomes possible, mainly, by the professional practice of the translator and interpreter of Libras (Brazilian Sign Language), that to do it presupposes a condition of formation that contemplates the political and social advances in deafness´s field. The profession, recently recognized in Brazil, is consolidated, among others, by the social movements of deaf community, in which one this professional reflects expressive participation. In this sense, the present research aims to investigate the professional development of Libras translator and interpreter, specifically, to analyze the significant formative experiences and to characterize the formative processes. To do so, based on an interview with open questions, the construction of the professional training of translators and interpreters working in a city in the interior of the State of São Paulo is investigated. The participants of this research, three translators and interpreters of Libras, were indicated by local deaf association and through an interview with a script validated in a pilot study they shared the formative experiences considered significant. The qualitative study sought to apprehend contents and meanings of the formative processes in the construction of professional training, and the investigation allowed to contemplate that this training can be occur in a plural ways by the community formation, by the systematized formation and by the formation in service. The analyzes allowed to visualize that the formative plurality of the subjects studied is constructed from a reflexive posture based on the knowledge of the languages, based on the participation of the professional in the deaf community, on the linguistic exchange with deaf fluent in Libras, as well as the sharing with interpreters and professionals more experients. It is also worth noting the professional development of the knowledge built from the systematic training, the possible knowledge of being produced and reproduced in the continuous formation, the participation in events of the area and in the formation throughout the performance. It is understood that the critical reflection of the professional doing is determined by the formative processes, which also determine the own critical reflection and the construction of the professional formation. It is necessary more investigations that contemplate the object of study in question, having seen the dynamic movement inherent the actions of inclusion of the deaf in society and the valorization of the profession in the labor market, this research sought to compose the theoretical framework of the area that has reached a broad level, mainly, after the legislation of recognition and appreciation of Libras. The knowledge reflected in the study, although the limits of the research, seek to contribute to the professional training of the translator an interpreter of Libras